Copper-catalyzed radical 1,2-oxysulfoximination of β,γ-unsaturated oximes for the synthesis of sulfoximine-substituted isoxazolines - Thete, Kishor R.; Vara, Vijay; Patel, Raj Y.; Muthukrishnan, M. (Organic & Biomolecular Chemistry, 2026)
Herein, we report a copper-catalyzed radical 1,2-oxysulfoximination of beta,gamma-unsaturated oximes. The transformation proceeds via intramolecular iminoxyl radical cyclization followed by interception with sulfoximines, enabling efficient access to sulfoximine-substituted isoxazolines in good yields under mild, oxidant-free conditions. The protocol operates at ambient temperature, exhibits a broad substrate scope with excellent functional group tolerance, and is readily scalable to gram quantities.